Factors influencing acceptance of human papillomavirus vaccine among young female college students in Thailand - Juntasopeepun P. (2014)
Objective: To determine knowledge and beliefs related to human papillomavirus (HPV), cervical cancer, and vaccination among young Thai women, and thereby identify independent predictors associated with acceptance of HPV vaccination. Methods: A convenience sample of 747 young women aged 18-24 years was recruited from universities and colleges located in the upper northern region of Thailand. An online questionnaire was performed to assess demographics; HPV and cervical cancer-related health characteristics; and knowledge and beliefs toward HPV and cervical cancer. Logistic regression analysis was used to determine independent predictors of HPV vaccine acceptance. Results: Knowledge about HPV and cervical cancer was moderate. The mean total knowledge score was 7.5 ± 3.8. Acceptance of the HPV vaccine was significantly associated with having received a recommendation for vaccination (odds ratio [OR] 2.12; 95% CI, 1.22-3.68); perceived susceptibility to disease (OR 1.37; 95% CI, 1.22-1.52); perceived benefits of vaccination (OR 1.33; 95% CI, 1.19-1.49); and perceived seriousness of disease (OR 0.90; 95% CI, 0.81-1.00). Conclusion: Understanding variables associated with acceptance of HPV vaccination may guide immunization initiatives and so increase the uptake rate among young Thai women. © 2012 International Federation of Gynecology and Obstetrics. Published by Elsevier Ireland Ltd. All rights reserved.